Compounds identified on hexane and dichloromethane extracts of Salicornia ramosissima - Isca, Vera M. S. (2014)
3rd Portuguese Meeting on Medicinal Chemistry and 1st Portuguese-Spanish-Brazilian Meeting on Medicinal Chemistry, Aveiro, 28-30 Novembro 2012.